Impact of Bariatric Surgery on Long-term Cardiovascular Risk: Comparative Effectiveness of Different Surgical Procedures - Oliveira, SC (2020)
Introduction: Several reports highlight bariatric surgery as an efficient and long-lasting strategy for weight loss. Herein, we aimed to evaluate the impact of bariatric surgery on 10-year cardiovascular disease (CVD) risk and to compare the effectiveness of different surgical procedures, employing the Framingham Risk Score (FRS). Methods: Retrospective longitudinal observational study of patients undergoing bariatric surgery. Data was assessed preoperatively and during a 4-year follow-up period. Results: We evaluated 1449 individuals, 85.2% female, age of 42.4 ± 10.6 years, and preoperative BMI of 44.3 ± 5.8 kg/m2; 58.0% underwent Roux-en-Y gastric bypass (RYGB), 23.4% sleeve gastrectomy (SG), and 18.6% adjustable gastric band (AGB). The 10-year CVD risk decreased 43.6% in the first postoperative year. The decrease in FRS was more pronounced in the RYGB group (50.5% in the first postoperative year) (p < 0.001). Although there was a subsequent slight increase in FRS during the follow-up period, the cardiovascular benefits were maintained when compared with baseline. For all surgical procedures, CVD risk showed a quadratic trend with a J-shaped curve. A negative interaction between the RYGB group CVD risk and time was observed (β = − 0.072 (95% CI, − 0.109; − 0.035)). In the RYGB group, FRS decreased more when compared with the SG and AGB groups and, from the second postoperative year onwards, increased more slowly, regardless of gender. The SG group showed similar trend as that of the AGB (β = − 0.002 (95% CI, − 0.049; 0.053)). Conclusion: Our study showed a significant reduction of 10-year CVD risk after bariatric surgery. This decrease was more pronounced in the first postoperative year, and RYGB was the procedure with the greatest decrease of the 10-year CVD risk.